2013
DOI: 10.7545/ajip.2013.2.1.097
|View full text |Cite
|
Sign up to set email alerts
|

Market Approach to Valuation Based on Technology Transfer Cases in Korea

Abstract: This study secured comparable sales transaction information of technology transfer corresponding to an active market conditions and proposes a method to assess the similarity of technologies with regard to comparability of technology transfer based on these cases information. In order to analyze the association and similarity between target technology and sales transactions, it proposes the significant factors affecting royalty decision and the cosine coefficient method by industry categories. It also proposes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…To resolve this issue, some research employed the real-life technology transaction dataset [5,6]. As mentioned in the introduction, these studies cannot handle the multiple response variables because they employed a univariate regression analysis.…”
Section: Market-based Technology Valuation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To resolve this issue, some research employed the real-life technology transaction dataset [5,6]. As mentioned in the introduction, these studies cannot handle the multiple response variables because they employed a univariate regression analysis.…”
Section: Market-based Technology Valuation Methodsmentioning
confidence: 99%
“…Quantitative methods that utilize statistical techniques based on actual technology transaction data are predominant in extracting the key influential factors. Sung et al and Kim et al [5,6] proposed a method for explaining the relationship between influential factors and technical fees and for selecting significant factors through linear regression analysis. Lee [13] performed a study that extracted and estimated the importance of influential factors related to technicality, ownership, and marketability through factor analysis, whereas Park [14] analyzed the differences in technical fees based on influential factors using ANOVA and t-tests.…”
Section: Identification Of Key Influential Factors In Technology Valu...mentioning
confidence: 99%
See 1 more Smart Citation
“…This paper investigates all 21 GRIs related to science and technology in Korea to identify the factors that impact technology transfer performance using panel data over five years, from 2015 to 2019. In Korea, various studies have investigated the factors influencing technology transfer [42][43][44][45][46], but research on GRIs has only recently begun to draw attention [45,47], and there has been some ambiguity in the interpretation of the analysis results, as previous literature has reported that the quantitative input of organizational resources into GRIs is not proportional to their quantitative performance [48] and that GRI performance depends on the nature of the institution or its particular mission [49,50]. This may be because GRIs differ in their specific missions, but it could also be due to the budget structure, which is greatly influenced by changes in government and R & D policies.…”
Section: Hypothesesmentioning
confidence: 99%
“…Past research on universities has reported that the number of research papers published has a positive relationship with technology transfer and technology fees [42,43,79]. However, a study of 50 universities and 34 government research institutes in Korea found no statistical significance in this relationship [78], and another study that analyzed 1222 national R & D projects reported that the number of research papers affects technology transfer but not technology fees.…”
Section: Research Capabilitiesmentioning
confidence: 99%